2020
DOI: 10.1007/s43039-020-00017-2
|View full text |Cite
|
Sign up to set email alerts
|

Hands off my data: users’ security concerns and intention to adopt privacy enhancing technologies

Abstract: As the number of data leak scandals and data infringements increase by the day, people are becoming more concerned than ever about their online security. As a result, software and applications designed to reduce, eliminate, or prevent unauthorized processing of users' online personal data, referred to as privacy enhancing technologies (PETs) are gaining momentum. Yet, research investigating what drives users' intention to adopt these technologies is still scant. Drawing on the Unified Theory of Acceptance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…A structured questionnaire developed using Google Module was shared among forty-one Facebook’s groups identified selecting thematic pages related to food and PDO/PGI products. The use of social networks for data collection is becoming mainstream in studies evaluating consumers’ adoption intentions of emerging technologies (Mangiò et al, 2020 ). Data were collected over 3 weeks in the second mid of August 2020.…”
Section: Methodsmentioning
confidence: 99%
“…A structured questionnaire developed using Google Module was shared among forty-one Facebook’s groups identified selecting thematic pages related to food and PDO/PGI products. The use of social networks for data collection is becoming mainstream in studies evaluating consumers’ adoption intentions of emerging technologies (Mangiò et al, 2020 ). Data were collected over 3 weeks in the second mid of August 2020.…”
Section: Methodsmentioning
confidence: 99%
“…Privacy concerns connect with the users’ dread that their personal information and data can be revealed to unauthorized parties. 28 In contrast, security concerns are connected with a person’s impression of how significant and satisfactory existing technical and lawful defensive measures guarantee uprightness, reliability of individual information, and confidentiality. 29 Privacy protection doesn’t ensure security protection, and vice versa.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This was confirmed by the qualitative study, which also offered new concepts to consider like fear of investigations and reduced accessibility of websites. Additional research on PETs in general found that besides privacy concerns, security concerns with regards to the used PET also play a crucial role in the adoption of PETs [36].…”
Section: Privacy Concerns Towards Privacy Enhancing Toolsmentioning
confidence: 99%